Krishnachandra Bhattacharyya’s Interpolation of Kant’s Idea of the “Self” - Babu, Roshni (Sophia, 2021)
Krishnachandra's re-articulation of Kant's transcendental system challenges Kant's conceptualization of 'apperceptive self' conceived as a logical function which is as well the precondition of all our knowledge claims. In Kant's framework, though this "unity of consciousness" is projected as a principle, which undertakes a foundational role as 'apperceptive I', it is capacitated with merely a logical function. Krishnachandra disagrees with Kant's reduction of function of the "self" to a logical process. This reduction would render knowledge of the "self" to be an inferential knowledge, thus making this derivation analogous to the proofs of the transcendental conditions of understanding and sensibility through the logical process of deductions. Krishnachandra's question is: whether this equation established between logical function of 'apperception' and the "self" will suffice to establish the "certitude" of knowledge claims. This is the first task Krishnachandra addresses in his work, Studies in Kant which is elucidated in the following section of this paper. Further, we will see how Krishnachandra’s exploration into the dynamics of this problem leads him to alternatively foreground the "unity", which is much sought by Kantian scholars, between the theoretical and the practical domains of Reason.